2020
DOI: 10.3390/foods9040477
|View full text |Cite
|
Sign up to set email alerts
|

Is Site-Specific Pasta a Prospective Asset for a Short Supply Chain?

Abstract: In the 2011–2012 season, variable-rate nitrogen (N) fertilization was applied two times during durum wheat vegetative growth in three field areas which differed in soil fertility in northern Italy. The quality traits of the mono-varietal pasta obtained from each management zone were assessed in view of site-specific pasta production for a short supply chain. To this purpose, semolina from cv. Biensur obtained from management zones with different fertility treated with N at variable rate was tested in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the experiment of Morari et al [13], the average protein content of the field was roughly 12% in both the cropping seasons considered, but the sandy areas fertilized with high nitrogen input were eligible for the premium quality with protein content, reaching a maximum value of 15%. The same areas revealed high HMW/LMW-GS ratios, which allow for obtaining dough with good technological characteristics as well as pasta with good sensory properties [14].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the experiment of Morari et al [13], the average protein content of the field was roughly 12% in both the cropping seasons considered, but the sandy areas fertilized with high nitrogen input were eligible for the premium quality with protein content, reaching a maximum value of 15%. The same areas revealed high HMW/LMW-GS ratios, which allow for obtaining dough with good technological characteristics as well as pasta with good sensory properties [14].…”
Section: Introductionmentioning
confidence: 77%
“…Technology has been demonstrated to be almost mature to apply automatic grain segregation during harvesting [15] and produce "site-specific" pasta [14]. The bottleneck of a "site-specific" pasta supply chain stays in the definition of the minimum grain stock required in manufacturing pasta.…”
Section: Introductionmentioning
confidence: 99%
“…Pasini et al [ 9 ] evaluated the technological properties of pasta production with semolina from cv Biensur, produced in zones with different fertility and treated with various rates of N, in comparison with commercial semolina (cv Aureo). The results obtained in this research demonstrated that the technological properties of Biensur semolina correlated to the low fertility zones treated with a high quantity of N. The derived pasta had characteristics similar to the ones obtained by semolina in cv Aureo.…”
mentioning
confidence: 99%